2021
DOI: 10.3390/s21103385
|View full text |Cite
|
Sign up to set email alerts
|

Complex Permittivity Characterization of Liquid Samples Based on a Split Ring Resonator (SRR)

Abstract: A complex permittivity characterization method for liquid samples has been proposed. The measurement is carried out based on a self-designed microwave sensor with a split ring resonator (SRR), the unload resonant frequency of which is 5.05 GHz. The liquid samples in capillary are placed in the resonant zone of the fabricated senor for high sensitivity measurement. The frequency shift of 58.7 MHz is achieved when the capillary is filled with ethanol, corresponding a sensitivity of 97.46 MHz/μL. The complex perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…On the other hand, several efforts have been devoted to improving the sensor quality factor. A three-stage coupled SRR structure was employed in [ 23 ], and an active feedback loop was introduced in [ 9 ] to increase the sensor resolution. However, the sensitivities of these sensors were relatively low due to their limited sensing area.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several efforts have been devoted to improving the sensor quality factor. A three-stage coupled SRR structure was employed in [ 23 ], and an active feedback loop was introduced in [ 9 ] to increase the sensor resolution. However, the sensitivities of these sensors were relatively low due to their limited sensing area.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, electrical impedance spectroscopy (EIS)-based sensors [ 20 ] and split-ring resonators metamaterial structures provide interesting alternatives, which have already proven useful for the evaluation of ethanol concentration [ 21 , 22 , 23 , 24 ] and are suitable for integration in microfluidic platforms [ 25 , 26 , 27 , 28 ]. However, few works have reported miniaturized EIS sensors with interdigitated (ID) electrodes and without any functionalization for ethanol sensing in liquid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have used these materials to design devices with high performances that can be used in mobile communication, medical structures and all wireless devices 14,16 . The first research work done as an application of metamaterial on liquid identification was done using split‐ring resonator (SRR) 17,18 . Then complementary split‐ring resonator (CSRR) was presented by Saadat et al 19 and open complementary split‐ring resonator (OCSSR) was proposed by Paris et al 5 The most recent work was carried out by Chuma et al 15 in which planar circular CSRR was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Some research works done on sensors dealing with the chemical solution were carried out by Salim et al 44 In addition, more recent research works were performed on studying the complex permittivity or compact permittivity of the liquids, 45,46 while other research works were focusing on biological and glucose characterization 47–50 . By examining the previously published works, 1–5,16–19,23–47 it was found that the sensitivity and sensor size are still the fundamental constraints to limit microwave sensors being widely adopted. Hence, in this article, a miniaturized and improved sensitive microwave sensor with two ports is proposed to address this issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation